Impact of interprofessional education on enhanced teamwork in ob-gyn emergency: results from a mixed-methods study - Yasmin, Haleema; Shoaib Malik,; Syed Moyn Aly, (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the impact of a 6-week interprofessional education programme on the teamwork perceptions of healthcare providers. Method: The mixed-method, quasi-experimental study was conducted at the Department of Obstetrics and Gynaecology. Jinnah Postgraduate Medical Centre, Karachi, from January to April 2022, and comprised healthcare professionals of either gender. Six interprofessional teaching sessions were conducted with as many diverse groups. The groups comprised obstetrician/gynaecologists, anaesthetists, midwives, operation theatre nurses, anaesthesia technicians, and emergency physicians. Baseline and post-intervention assessment was done using the Teamwork Perception Questionnaire. Qualitative data was collected through in-depths interviews and focussed group discussions. Data was analysed using SPSS 26. Results: Of the 60 participants, 36(60%) were females and 24(40%) were males. The overall mean age was 35.46±5.93 years. There were 10(20%) subjects in each of the six groups. At baseline, emergency physicians had the highest score 84.00±15.78, while post-intervention, anaesthetists had the highest mean score 178.00±16.26. The highest difference between baseline and post-intervention scores was noted for midwives 136.00±0.12. The difference was significant across all the subscales for operation theatre nurses (p<0.05). In the other five groups, the difference post-intervention was significant for all aspects (p<0.05) except situation monitoring (p>0.05). Qualitative data noted effective communication and good leadership as the most important core components, and highlighted that various factors could fortify interprofessional education implementation. Conclusion: Interprofessional education and training sessions were found to be well accepted, signifying positive engagements towards teamwork, with the participants exhibiting a good grasp of teamwork skills, including leadership, management and communication, in obstetric crises. Key Words: Communication, Interprofessional education, Leadership, Teamwork.